2019
DOI: 10.3389/fphar.2019.00747
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Study of Transcriptome Changes in the Mice Lumbar Spinal Cord After the 30-Day Spaceflight and Subsequent 7-Day Readaptation on Earth: New Insights Into Molecular Mechanisms of the Hypogravity Motor Syndrome

Abstract: The hypogravity motor syndrome (HMS) is one of the deleterious impacts of weightlessness on the human body in orbital space missions. There is a hypothesis that disorders of musculoskeletal system as part of HMS arise in consequence of changes in spinal motor neurons. The study was aimed at bioinformatic analysis of transcriptome changes in lumbar spinal cords of mice after a 30-day spaceflight aboard biosatellite Bion-M1 (space group, S) and subsequent 7-day readaptation to the Earth’s gravity (recovery group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…There are several consequences to living in low-Earth orbit. These include edema due to fluid and cardiovascular deconditioning 1 , myelin degeneration 2 , disorientation and motor control deficits 3 , 4 , visual deficits 5 , endocrine and hormonal alterations 6 , muscle tone wasting 7 , and bone loss due to lack of mechanical loading 8 . Upon return to Earth, there is a period of readaptation that includes acute motion sickness, unsteadiness, imbalance due to gravity-induced vestibular fluid shifts 9 , and blood pressure changes 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several consequences to living in low-Earth orbit. These include edema due to fluid and cardiovascular deconditioning 1 , myelin degeneration 2 , disorientation and motor control deficits 3 , 4 , visual deficits 5 , endocrine and hormonal alterations 6 , muscle tone wasting 7 , and bone loss due to lack of mechanical loading 8 . Upon return to Earth, there is a period of readaptation that includes acute motion sickness, unsteadiness, imbalance due to gravity-induced vestibular fluid shifts 9 , and blood pressure changes 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…After 30 days of space flight, in motor neurons of mice lumbar spinal cords, immunoexpression of the proteins responsible for synaptic transfer of a nervous impulse and proteins of heat shock proteins decreased [19]. In general, these results support the assumption that weightlessness affects the motor neurons of the spinal cord, which is a leading factor in HMS [8].…”
Section: Introductionmentioning
confidence: 66%
“…In the transcriptional profile analysis of the mice spinal cord after 30 days of space flight and readaptation, 178 genes, involved in 60 metabolic and signal pathways, with changed expression, were detected. A total of 118 genes of the increased expression and 60 of the decreased expression were revealed [8]. In the study of Islamov et al [23], cytoskeletal proteins were shown to participate in spinal cord alteration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations